2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259425
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Heat Transfer Model of Deep Brain Stimulation Induced Temperature changes

Abstract: There is a growing interest in the use of chronic deep brain stimulation (DBS) for the treatment of medically refractory movement disorders and other neurological and psychiatric conditions. Fundamental questions remain about the physiologic effects and safety of DBS. Previous basic research studies have focused on the direct polarization of neuronal membranes by electrical stimulation. The goal of this paper is to provide information on the thermal effects of DBS using finite element models to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 20 publications
1
36
0
7
Order By: Relevance
“…It is possible that the high-frequency blocking stimulation modulates the glial buffering or ion pump resulting in a nerve conduction failure. Furthermore, due to the kHz stimulation the Joule heating effect might start to play a role, although a recent theoretical analysis (Elwassif et al, 2006) showed that it is negligible at frequency of 185 Hz during deep brain stimulation. A more realistic axonal model may reveal other nerve blocking mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the high-frequency blocking stimulation modulates the glial buffering or ion pump resulting in a nerve conduction failure. Furthermore, due to the kHz stimulation the Joule heating effect might start to play a role, although a recent theoretical analysis (Elwassif et al, 2006) showed that it is negligible at frequency of 185 Hz during deep brain stimulation. A more realistic axonal model may reveal other nerve blocking mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The radius of the head model sphere (HMS) is 9 cm, and the IAS has 1 cm radius. The average value of sound speed is 1500 m/s for the supposed medium, and the temperature of the head (model) takes the average value of 37 • C or 310 • K [19,20]. The results of the computation are depicted in Table 1 and Figures 2, 3, 4, 5, 6 and 7 where the Q ratio values, from simulations of different positions of the IAS and different frequencies, are shown.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Genlik H a r c a n a n G ü ç ( m W / m m 3 Göz içi bölgeye yerleştirilerek uzun dönem vücutta kalması planlanan cihazların neden olacağı sıcaklık yan etkilerini tasarım aşamasında modelleme çalışmalarıyla incelemek kritik önem taşımaktadır. Sıcaklığa duyarlı olan retina dokusundaki sinir hücrelerinde meydana gelebilecek yüksek sıcaklık değişimleri sıcaklığa bağlı olan, gerilim kontrollü kanallar gibi, hücre zarı özelliklerini ve sinirsel ağı etkileyerek hücre ölümlerine neden olabilir [39,40]. Normal vücut sıcaklığından 3 derece yüksek sıcaklık artışlarının çeşitli fizyolojik anormalliklere neden olacağı rapor edilmiştir [40,41].…”
Section: Merkez-ağırlıklı Zaman Kaymalı Uyartım Stratejisi (Central-wunclassified